The Role of NMDA Receptors in the Effect of Purinergic P2X7 Receptor on Spontaneous Seizure Activity in WAG/Rij Rats With Genetic Absence Epilepsy - Doǧan, Elif; Aygün, Hatice; Arslan, Gökhan; Rzayev, Emil; Avcı, Bahattin; Ayyıldız, Mustafa; Ağar, Erdal (Frontiers in Neuroscience, 2020)
P2X7 receptors (P2X7R) are ATP sensitive cation channels and have been shown to be effective in various epilepsy models. Absence epilepsy is a type of idiopathic, generalized, non-convulsive epilepsy. There are no studies on the effects and interaction of P2X7R and glutamate receptor NMDA on absence epilepsy. Therefore, we aimed to investigate the electrophysiological and biochemical aspects of P2X7R agonist BzATP and antagonist A-438079 and NMDA antagonist memantine in WAG/Rij rats. In the present study, 56 male WAG/Rij rats aged 6-8 months were used. Electrodes were placed on the skulls of the animals. BzATP (50 μg, 100 μg i.c.v); A-438079 (20 μg, 40 μg i.c.v.); memantine (5 mg/kg i.p.) and interaction groups were set up, then ECoG recordings were taken for three hours. The records were examined in terms of number and duration of spike and slow-wave discharges (SWDs) and amplitude. Rats were decapitated for biochemical analysis and the right and left hemisphere, cerebellum and brainstem were separated; blood samples were taken; advanced protein oxidation products (AOPP), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), glutathione peroxidase (GPx) and glutathione reductase (GR) levels were measured. BzATP and A-438079 did not alter measured parameters of SWDs in WAG/Rij rats whereas memantine reduced them which is considered anticonvulsant. P2X7R agonist BzATP did not change the anticonvulsant effect of memantine on SWDs, while antagonist of P2X7R, A-438079 decreased the effect of memantine. Administration of BzATP changed only SOD and GR levels in hemispheres. A-438079 did not alter any of the biochemical parameters. Memantine reduced the levels of MDA, GSH and GR while increased the level of CAT in the cerebrum. BzATP + memantine group affected CAT, GSH and GR levels without changing MDA and SOD levels. Electrophysiologic and biochemical results of present study show that P2X7R does not affect either SWDs seen rats in WAG/Rij. Memantine showed anticonvulsant and antioxidant actions in absence epilepsy. Agonist of P2X7R reversed some of oxidant parameters and antagonist of P2X7R reduced anticonvulsant action of memantine suggesting a partial interaction between P2X7R and NMDA systems in WAG/Rij rats.